Multi-Scale Information Collaborative Management Method in Hierarchical Construction Projects Based on Building Information Modeling - Xuefeng Zhao; Wenkai Yan; Yu Xia; Zhe Sun; Mengxuan Li; Yan Bao; Qiankun Guo (Applied Sciences)
Building Information Modeling (BIM) has been widely adopted in the Architecture, Engineering, and Construction (AEC) industry for information modeling and project-level based on information collected from multiple sources. Unfortunately, multi-scale building information is often organized in different formats according to different data management protocols, making it a challenge to extract the data needed for effective decision-making by different project participants. This study proposed a method for the effective exchanges of multi-scale information through BIM, This method includes establishing an information management protocol between microscale and mesoscale through format conversion, standard unification, and contract constraint, and establishing an information management protocol between mesoscale and macroscale through model analysis, data integration, and institutional guarantee. The three paths of model, data, and management are used to link up the collaborative management of information in the three dimensions of individual, group, and region. The authors validated the proposed method using a case study of a project in Xiong’an New District in China as an example. Results show that the proposed method could help with the transmission and utilization of multi-scale building information using BIM for effective project management, which in turn enables the urban planners to have overall control over the information of urban construction projects.